Personal consumption in Poland in global crisis conditions - Sobczyk, G. (Видавництво Львівської політехніки, 2013)
The article presents a consumer economic situation of Polish households in the global financial crisis conditions. Determinants of an personal consumption and its chosen measures in the years 2008-2011 were shown. The thesis concerning the significant role of consumption in the growth of economy of a country gained despite of recessionary occurrence was substantiated. Представлена споживча економічна ситуація польських домогосподарств в умовах глобальної фінансової кризи. Висвітлено детермінанти особистого споживання і його індикатори у період 2008–2011 рр. Висвітлено тези про велику роль особистого споживання у зростанні економіки країни.
Особисте споживання у Польщі в умовах глобальної кризи
Keywords: consumption; crisis; households; споживання; криза; домашні господарства